Trajetórias de aprendizagem de alunos de ensino médio: produção de significados em um curso introdutório de física térmica - Gabriel Dias de Carvalho Junior (2005)
The objective of this research is to accompany the ways that are followed for secondary level students, here they are designated learning trajectories, in a Thermic Physics introductory course. We have wished to investigate, (1) the role that explanatory models are elaborated by students alongside of didactic intervention they fulfill on Thermic Physics concept and relation learning and (2) the function which kinetic-molecular model perform on understanding of the Thermic Physics conceptual relations. Our fundamental hypothesis is one of that, during the teaching and learning formal process, student elaborates and modifies his explanatory models about the subject on discussion. These models serve as base for new meaning construction during all process, supporting or creating obstacles to the following learning. Therefore, we look for searching the evolution of explanatory models that are elaborated by students in class-room actual situations. The fundamental theoretical mark from that research is the conceptual field theory by VERGNAUD (1990, 1993 and 1998), because it is a theory which, we can see, better and better presents elements in order to analyze the subject-in- action, focus of our search. For that author, the knowledge is organized on conceptual fields, which on the part of learner, it goes on happening alongside of an extensive period of time, by means of experience, maturity and learning (MOREIRA, 2002). A pre-tested teaching sequence has been guided in order to answer to the characteristic of that research. The application of this sequence has occurred alongside of months from 2003 August to October in a high school second year classroom. Students were divided into groups and one of the groups was chosen, with seven students, for a more intensive accompaniment. In two moments alongside of process, students have individually answered to the questions about the subjects in discussion. Classes were filmed and, after transcription, each activity and exchanges among students were evaluated. After seven months at the end of teaching sequence application, interviews were led with the researched students. Therefore, we count the following sources for collection of data: (1) answers have been given by students to the constant questions and problems on teaching sequence; (2) in writing registration after each applied activity of the accompanying group collective constructions which were gathered each applied activity; (3) interaction moments among students of group and between them and the teacher, they are obtained by means of class filming and (4) audio and video registers of the interviews for the students of accompanying group. Using Vergnaud´s conceptual field theory, we seek, on concepts-in-action and theorems-in-action elaborated by students, the elements allowed to compose their learning trajectories. We hope obtained results from that research can serve as inspiration for new thrusts for other teachers on other science contents topics. This fact can contribute in order that teaching with constructivism bases reach fully in class- room background, allowing more significants methods to the students for approximating of the knowledge objects.